Just giving : why philanthropy is failing democracy and how it can do better - Reich, Rob (Princeton University Press, 2018)
Asks what attitude and what policies democracies should have concerning individuals who give money away for public purposes; and argues that the aims of mass giving should be the decentralization of power in the production of public goods, such as the arts, education, and science.